2011
DOI: 10.3892/ol.2011.277
|View full text |Cite
|
Sign up to set email alerts
|

Radio-sensitization of the murine osteosarcoma cell line LM8 with parthenolide, a natural inhibitor of NF-κB

Abstract: Abstract. Nuclear factor (NF)-κB has been shown to be associated with cancer resistance to radiotherapy (RT), and is constitutively active in the murine osteosarcoma cell line, LM8. Parthenolide has been reported to show antitumor activity through inhibition of the NF-κB pathway. In this study, we investigated the radio-sensitizing activity of parthenolide. We established Luc-LM8, a stable transfectant reporter construct of NF-κB transcriptional activity into LM8. Luc-LM8 maintained the malignancy observed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…The posterior irradiation further diminished osteosarcoma cell viability [ 69 ]. Similar findings were detected in LM8 transfected with a reporter construct of NF–κB, Luc–LM8, in vitro and in vivo [ 78 ]. Importantly, synergy between parthenolide and ionizing radiation was observed against the cancer stem cells subpopulation of LM7 [ 69 ].…”
Section: Parthenolidesupporting
confidence: 80%
See 1 more Smart Citation
“…The posterior irradiation further diminished osteosarcoma cell viability [ 69 ]. Similar findings were detected in LM8 transfected with a reporter construct of NF–κB, Luc–LM8, in vitro and in vivo [ 78 ]. Importantly, synergy between parthenolide and ionizing radiation was observed against the cancer stem cells subpopulation of LM7 [ 69 ].…”
Section: Parthenolidesupporting
confidence: 80%
“…For these reason, radiosensitization strategies followed by a posterior chemotherapy are under investigation. It is established that the expression of NF–κB contributes to osteosarcoma radioresistance [ 70 , 78 ]. Zuch et al [ 63 ] found enhanced cell death of an aggressive derivative of Saos–2, LM7, when parthenolide and ionizing radiation were given together.…”
Section: Parthenolidementioning
confidence: 99%
“…Osteosarcoma is a primary malignant bone tumor, commonly demonstrates significant radioresistance and high metastatic potential [181]. In osteosarcoma, human and murine cell line, resistance to radiotherapy has been associated with NF-κB activity [182,183]. Pretreatment with PN synergistically suppressed cell proliferation and potentiated apoptosis induced by ionizing radiation in osteosarcoma cells.…”
Section: Parthenolide Combined With Radiotherapymentioning
confidence: 99%
“…This effect was connected to the ability of PN to induce oxidative stress [182]. PN with irradiation treatment inhibited osteosarcoma tumor growth in mice more effective compared to PN or irradiation alone [183]. PN enhanced X-ray sensitivity of radiation resistant CGL1 (HeLa hybrid) cells [30].…”
Section: Parthenolide Combined With Radiotherapymentioning
confidence: 99%
“…Our system has a number of advantages, i.e. it is a fully human preclinical model, in contrast to other murine-based sarcoma cell line models 24,25,26,27 . Furthermore, whilst the confirmation of the establishment of STS primary cultures, achieved by cytomorphological, immunohistochemical and molecular cytogenetic evaluation, with the support of an experienced sarcoma pathologist, is mandatory in our protocol, this is not always the case for other STS primary culture models.…”
mentioning
confidence: 99%